Dokumenty urzędowe i dokumenty prywatne jako środki dowodowe w postępowaniu cywilnym - Czerwińska, Berenika (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
Hearing of evidence tends to establish the facts of relevance to the outcome of the case, therefore this is the essence of civil procedure. Although there is no hierarchy of evidence in the Code of Civil Procedure, the legislature implemented special preferences for documentary evidences, which use a number of legal presumptions. The purpose oft his article is to analyze documentary evidence, in particular, the attempt to define the concept of a document, discussion about official and private documents, as well as an indication of their probative value
Keywords: dokument urzędowy; dokument prywatny; dokument elektroniczny; domniemanie